Acetylation of Glycerol Catalyzed by CaO as Octane Booster in Gasoline Fuel - Nugraheni, Ika Kusuma; Sokheh, Sahidin; Artika, Kurnia Dwi (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
Glycerol, a byproduct of biodiesel production, can be transformed into value-added compounds such as triacetin, which serves as an effective octane booster in gasoline. This study investigates the acetylation of glycerol with acetic acid using calcium oxide (CaO) as a heterogeneous catalyst. Catalyst concentrations of 1%, 2.5%, 5%, 7.5%, and 10% were tested under reaction conditions of 100C for 180 minutes. The resulting products were analyzed using gas chromatographymass spectrometry (GC-MS) to identify acetylated derivatives. Among the tested conditions, 5% CaO yielded the highest triacetin content. The acetylated product was then blended into gasoline at a 5% concentration. Fuel testing showed an increase in the Research Octane Number (RON) from 84 (pure gasoline) to 93 with the addition of triacetin, along with slight increases in fuel density and viscosity. These findings highlight the potential of CaO-catalyzed glycerol acetylation for producing high-performance fuel additives.